Transformation of Acinetobacter calco-aceticus (Bacterium anitratum) - Juni, Elliot (1969)
A highly efficient transformation system has been demonstrated in a strain of Acinetobacter calco-aceticus (Bacterium anitratrum). During mixed growth of various stable, unencapsulated, mutant strains, deoxyribonucleic acid (DNA) is liberated and fully encapuslated transformants can be isolated. Purified DNA preparations have been used to transform suitable recipient mutant strains for ability to synthesize capsules, ability to dispense with a growth factor requirement, and resistance to streptomycin. When the wild-type strain is deprived of its capsule, either by mechanical stripping or by mutation, the unencapsulated cells tend to form large clumped masses. A nonclumping mutant of an unencapsulated strain has been isolated. When ability to synthesize capsules is transformed into this nonclumping strain, the resultant cells no longer form chains, unlike the wild-type encapsulated strain. It appears likely that the occurrence of transformation during growth of mixed cultures, with glucose or gluconate as the carbon source, may be the result of osmotic rupture resulting from the inability of unencapsulated strains to oxidize triose phosphates as fast as they are formed. The finding of transformation in Acinetobacter may provide an additional useful organism for the study of this mode of genetic transfer since this strain grows well in a simple mineral medium containing a single oxidizable source of carbon. Furthermore, no special supplementary factors seem to be required for transformation to take place.